2017
DOI: 10.3847/1538-4357/aa6c27
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Superluminous Supernovae Using the Magnetar Engine Model and Implications for Their Connection with Gamma-Ray Bursts and Hypernovae

Abstract: By fitting the bolometric light curves of 31 super-luminous supernovae (SLSNe) with the magnetar engine model, we derive the ejecta masses and magnetar parameters for these SLSNe. The lower boundary of magnetic field strengths of SLSN magnetars can be set just around the critical field strength B c of electron Landau quantization. In more details, SLSN magnetars can further be divided into two subclasses of magnetic fields of ∼ (1 − 5)B c and ∼ (5 − 10)B c , respectively. It is revealed that these two subclass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 109 publications
3
61
0
Order By: Relevance
“…For example, Bersten et al (2016) must be powered by magnetars with P 0 ≈ 1-10 ms and 10 13 -10 15 (see, e.g., Inserra et al 2013;Nicholl et al 2014;Liu et al 2017b;Nicholl et al 2017;Yu et al 2017 ), indicating that the values of P 0 and B p play a crucial role in determining the peak luminosities of SLSNe. When P 0 10 ms and B p is a few 10 14 G, the magnetarpowered SNe are luminous (Wang et al 2015b); when P 0 10 ms and B p is a few 10 16 G, the magnetars can explain the LCs of some SNe Ic-BL (Wang et al 2016a; see also Chen et al 2017), while Cano et al (2016) suggested that most GRB-SNe are powered by radioactive heating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bersten et al (2016) must be powered by magnetars with P 0 ≈ 1-10 ms and 10 13 -10 15 (see, e.g., Inserra et al 2013;Nicholl et al 2014;Liu et al 2017b;Nicholl et al 2017;Yu et al 2017 ), indicating that the values of P 0 and B p play a crucial role in determining the peak luminosities of SLSNe. When P 0 10 ms and B p is a few 10 14 G, the magnetarpowered SNe are luminous (Wang et al 2015b); when P 0 10 ms and B p is a few 10 16 G, the magnetars can explain the LCs of some SNe Ic-BL (Wang et al 2016a; see also Chen et al 2017), while Cano et al (2016) suggested that most GRB-SNe are powered by radioactive heating.…”
Section: Discussionmentioning
confidence: 99%
“…When P 0 10 ms and B p is a few 10 14 G, the magnetarpowered SNe are luminous (Wang et al 2015b); when P 0 10 ms and B p is a few 10 16 G, the magnetars can explain the LCs of some SNe Ic-BL (Wang et al 2016a; see also Chen et al 2017), while Cano et al (2016) suggested that most GRB-SNe are powered by radioactive heating. Wang et al (2015b) emphasized the role of P 0 while Yu et al (2017) highlighted the role of B p . We suggest that the more reasonable scheme discussing the factors influencing the peak luminosities and the shapes of magnetar-powered SNe and SLSNe is to take into account both of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 compares our predicted NS rotation periods (the same as shown in Figure 3) to observationally inferred magnetar rotation periods, as a function of ejecta mass. Yu et al (2017) and Blanchard et al (2020) estimated ejecta masses, magnetar rotation periods, and magnetar field strengths by modeling SLSNe Ic light curves assuming they are powered by dipole spin-down of a rapidly rotating magnetar. Their inferred rotation periods and ejecta masses (teal/green stars in Figure 5) show a similar trend to our predictions, with higher ejecta masses corresponding to more rapidly rotating magnetars.…”
Section: Comparison With Observed Supernovaementioning
confidence: 99%
“…One possibility for this discrepancy is that our model predicts too much AM extraction from massive stellar cores, and that NSs are born rotating several times faster than our predictions. Another possibility is that the inferred ejecta masses of Yu et al (2017) and Blanchard et al (2020) are systematically too small. They used semi-analytic light curve models with a constant opacity, assuming a magnetar central engine.…”
Section: Comparison With Observed Supernovaementioning
confidence: 99%
“…We find that the B p values of the magnetars in the lGRBs are averagely smaller than that in the sGRB by about one order of magnitude. Superluminous supernovae (SLSNe) are very similar to hypernovae associated with lGRBs (van den Heuvel & Portegies Zwart 2013; Lunnan et al 2015;Nicholl et al 2015Nicholl et al , 2016Japelj et al 2016;Jerkstrand et al 2017;Yu et al 2017;Prajs et al 2017;Inserra et al 2018). In particular, Lunnan et al (2015) showed that the host galaxies of GRBs and SLSNe Type I share many common properties, e.g.…”
Section: Magnetic Field Strength and Jet Formation In Newborn Magnetarsmentioning
confidence: 99%